Abuse of Authority by a Branch Manager in the Transfer of Customer Funds as Illegal Credit Collateral: A Study of Decision Number 134/Pdt.G/2025/PN Jkt.Pst - Gusti Bintang Maharaja; Chelsea Kairadinda Adam; Firda Amalia (Media Hukum Indonesia (MHI), 2026)
Abuse of authority by bank branch managers represents a form of governance failure that not only harms customers individually but also undermines public trust in the national banking industry. This study juridically analyzes the case of abuse of authority committed by the Branch Manager of PT Bank Maybank Indonesia Tbk, Cilegon Branch, in Case Number 134/Pdt.G/2025/PN Jkt.Pst, in which customer funds amounting to IDR 30 billion were unilaterally converted into cash collateral for another party’s credit facility without the knowledge of the legitimate owner of the funds. Using a normative research method through statutory and case approaches, this study integrates an analysis of bank credit policy materials with a review of court decisions. The results of the study indicate that the actions of the branch manager systematically violated the prudential banking principle, disregarded the 5C and 7P credit analysis procedures, and weakened the segregation of duties mechanism that should function as an internal control safeguard. Furthermore, this study finds that the doctrine of vicarious liability, as regulated under Article 1367 of the Indonesian Civil Code (KUHPerdata), provides a strong legal basis for imposing civil liability on the bank as a corporation for unlawful acts committed by its branch manager, particularly when the bank fails to prove that it had implemented adequate preventive measures